Drawing Spaniards in the Philippines: Displacement, Brutalization, and the Dissident Eye of Ignacio del Villar - Casanova, Rocío Ortuño (Archīum Ateneo, 2024)
This article explores the Spanish colonization of the Philippines and their colonial culture and society as portrayed in the comic strips by Ignacio del Villar, a Spanish cartoonist who drew for Philippine colonial magazines in Spanish. His pictures, whose principal audience was the Spanish-speaking community of Manila in the late nineteenth and early twentieth centuries, satirize the alienation of the Western individual in the Philippines. His mockery of the generalized colonial attitude of “monarch of all I survey” links del Villar with dissident colonial accounts, as discussed by Mary Louise Pratt in Imperial Eyes. This article inquires on the reasons why del Villar seemingly veered away from traditional colonial discourses, resulting in the mockery of the self-image of social superiority that Spanish residents in the Philippines strived to maintain in a complex society where class and origin were difficult notions to define.